The Masterpiece of Abdullah Ibn Mubarak - Ziyodullayevich, Ulugmuratov Akmal (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
There are several copies of "Zuhd" compiled by Abdullah ibn Mubarak, the originals of all of which were obtained from the library of Valiuddin Jorullah in Istanbul. Its history dates back to the seventh century. Because there it is recorded that this book was samo'an, that is, written by the author in the year 600 (Hij). After this copy passed from hand to hand and finally fell into the hands of this Valiuddin Jarullah, he dedicated this copy to the cause of Allah.